Analisis Kepemimpinan Spiritual, Perilaku Kerja Spiritual, dan Kesadaran Lingkungan Terhadap Environmental Passion - Yuni Siswanti; Ahmad Muhsin; Laila Nafisah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
From synthesizing theories of leadership, spirituality, and pro-environmental behavior, this research built and tested a theoretical model linking spiritual leadership with employee pro-environmental behavior via one moderating variable. Data were collected from 37 heads of families occupied Winongo Ex Station in the former railway line in Glondong Tirtonirmolo village, Kasihan Bantul, Yogyakarta after The earthquake that occurred on May 26, 2006 in Yogyakarta.The location occupied was the Sultan Ground (SG) land. In the course of time, the residents asked permission from the court to get the right to use the land or called Serat Kekancingan. The Yogyakarta Palace gave the answer that the Permit had been given to someone who in fact never lived, the land also became the object of buying and selling by irresponsible persons, and someone acted on behalf of the palace expert's interest and claimed to be the legitimate heir to the land. We use survey to collected data from 37 respondents and continue use Participatory Rural Appraisal method (PRA) (A. Muhsin, D. S. Hapsoro, and Y. Siswanti,2018) which is packaged in the form of Focus Group Discussion (FGD) in its participatory approach. We found that, spiritual leadership positively affected workplace spirituality (H1 was supported). Workplace spiritually positively affected environmental passion (H2 was supported). Environmental awareness moderated the effect workplace spirituality and environmental passion (H3 was supported).